Analisis Potensi Ekonomi di Provinsi Sulawesi Tenggara - Permana, Teguh; Djauhar, Asri; Puspitaningsih, Andriani; Surianti (Ebisma (Economics, Business, Management, & Accounting Journal), 2023)
This study aims to determine the economic potential in Southeast Sulawesi province based on 17 economic sectors. This research is a quantitative study using the LQ analysis tool. Based on research results, the economic potential in Southeast Sulawesi province is relatively stable as indicated by the LQ value, where the mining and quarrying sector occupies the first position as the leading sector. The implication is that the mining and quarrying sector is still a priority in supporting the economy in the province of Southeast Sulawesi. This must be supported by involving more local communities so that the impact can be felt more for the people of Southeast Sulawesi in particular and Indonesia in general